Toward a Better Understanding of What Makes Positive Psychology Interventions Work: Predicting Happiness and Depression From the Person × Intervention Fit in a Follow‐Up after 3.5 Years. Issue 1 (26th November 2014) - Proyer, René T.; Wellenzohn, Sara; Gander, Fabian; Ruch, Willibald
Abstract : Background: Robust evidence exists that positive psychology interventions are effective in enhancing well‐being and ameliorating depression. Comparatively little is known about the conditions under which they work best. Models describing characteristics that impact the effectiveness of positive interventions typically contain features of the person, of the activity, and the fit between the two. This study focuses on indicators of the person × intervention fit in predicting happiness and depressive symptoms 3.5 years after completion of the intervention.Methods: A sample of 165 women completed measures for happiness and depressive symptoms before and about 3.5 years after completion of a positive intervention (random assignment to one out of nine interventions, which were aggregated for the analyses). Four fit indicators were assessed: Preference; continued practice; effort; and early reactivity.Results: Three out of four person × intervention fit indicators were positively related to happiness or negatively related to depression when controlled for the pretest scores. Together, they explained 6 per cent of the variance in happiness, and 10 per cent of the variance of depressive symptoms.Conclusions: Most tested indicators of a person × intervention fit are robust predictors of happiness and depressive symptoms—even after 3.5 years. They might serve for an early estimation of the effectiveness of a positive intervention.